TINJAUAN TERHADAP PROSTITUSI BERKEDOK PANTI PIJAT DI KOTA SAMARINDA - Murliana, Murliana (Journal of Law ( Jurnal Ilmu Hukum ), 2018)
Abstract      Prostitution that often occurs in massage parlors in the city of Samarinda is common in the community and has even been passed down from previous generations.              Type of research in this paper uses normative legal research and uses the Law-Invitation approach and the Conceptual approach.              Results showed that the act of prostitution that was cultivated / provided by massage parlors, was more focused on someone who runs the prostitution business, namely pimps. Clearly and firmly running a business in the practice of prostitution can be punishable by imprisonment if their actions fulfill the elements of the Criminal Code. From these actions there are several factors that have led to the practice of prostitution under the guise of massage parlors. Efforts made by the government to tackle prostitution under the guise of massage parlors are through prevention through the provisions stipulated in the Samarinda City Regulation Number 03 of 2009 concerning Prevention and Control of HIVS and AIDS in Samarinda City as well as enforcement of Samarinda City Regulation Number 18 of 2002 concerning Control and Prevention of Commercial Sex Workers in the Samarinda City Region. A Commercial Sex Worker in the practice of prostitution cannot be convicted due to the lack of legal provisions that can ensnare a Commercial Sex Worker related to the prosecution of cases of prostitution, therefore legal provisions that strictly regulate the case of the Commercial Sex Worker are needed.